Legal Educational Assistance For Drug Addicts Through Integrated Rehabilitation Assessment In West Sumatra - Azwar Azwar; Alamsyah Adi Putra (Jurnal Masyarakat Mengabdi, 2026)
Drug abuse in Indonesia has reached 2.11% or 4.15 million people in 2025, with productive age groups and adolescents as the most vulnerable population. This community service aims to provide legal education assistance to addicts, abuse victims, and drug users through Integrated Assessment to obtain rehabilitation rights. The implementation method uses a qualitative approach with in-depth document analysis, legal facts, evidence, and medical and legal education assessment of six respondents. The results show that all respondents (aged 19-44, with high school and university student backgrounds) meet rehabilitation criteria based on SEMA No. 4 of 2010. The Integrated Assessment Team recommended three months of inpatient rehabilitation for five respondents and 12 sessions of outpatient rehabilitation for one university student. The legal education provided includes an understanding of Law No. 35/2009, SEMA No. 4/2010, and victims' rights, with an average increase in respondents' understanding of 65%. This activity contributes significantly to victim recovery while serving as a learning opportunity for the education sector regarding the prevention and handling of drug cases among students. The novelty of this activity lies in the integration of legal education in the Integrated Assessment process.